Ectopic eruption: Management of a partial mandibular lateral incisor transposition in a case report - Amirhossein Mirhashemi (Dental Hypotheses, 2016)
Introduction: tooth transposition is a rare condition especially in the mandibular arch. Management of this condition is so hard, complicated and unknown for most of the clinicians. Case report: In this report we describe a case of orthodontic management of a partial mandibular left lateral incisor and canine transposition. We used a modified lingual arch appliance for initial correction of tooth transposition, more detailing was achieved by fix treatment. Discussion: Early detection of this anomaly is very important. Providing panoramic radiography to assess the developing dentition during the age of 6 to 8 years is an apropos forethought.